La educación superior rural en Colombia: un estado del arte - Pérez Verano, Jonathan (2025)
This paper presents a state-of-the-art review of rural higher education in Colombia, focusing on academic work conducted between 2015 and 2023. Employing a qualitative approach and drawing on Pierre Bourdieu’s methodology of the field of knowledge, a systematic documentary review was carried out. The analysis identified two main categories of work: Within the academy and Outside the academy, each further subdivided to provide a nuanced examination of the strengths and weaknesses of the reviewed studies. The findings highlight significant gaps and challenges in the field. The paper concludes by emphasizing the urgent need for more inclusive and diversified public policies to address persistent educational inequalities in rural areas.